Quadricuspid Aortic Valve Visualized by Three-Dimensional Transthoracic Echocardiography - Eser Acar; Tayfun Sahin; Irem Yılmaz; Umut Celikyurt (Case Reports in Cardiology)
Quadricuspid aortic valve is a rare congenital anomaly that may cause aortic regurgitation. A 77-year-old male patient was referred to our clinic with complaints of stable angina pectoris. We report a case of a quadricuspid aortic valve diagnosed by 3-dimentional transthoracic echocardiography.